"I remember it like it was interesting." – Zur Theorie von Salienz und Pertinenz - Purschke, Christoph (Linguistik Online, 2014)
This text is devoted to theoretical aspects of the perception and evaluation of linguistic phenomena as part of listener judgments about language in social interaction. First, salience (perceptual conspicuity) and pertinence (subjective situational relevance) are considered as fundamental categories and subprocesses of listener judgments, in line with Purschke's (2011) perceptual judgment theory. This is followed by a detailed discussion of salience-relevant parameters that concentrates on the two constitutive elements of salience evaluations, salience potential (phenomenon-based usage) and salience perception (listener-based interpretation). In a second step, the internal structure of pertinence judgments based on relevance is remodeled and located within a theory of judgment deductive scheme through reference to two well-known relevance theories (Schütz/Luckmann 1979; Sperber/Wilson 1995). The paper concludes by proposing and exploring an integrative term to define the main subject of salience- and pertinence-based listener judgments about language – socio-pragmatic indexicality.